Analysis of Exposure of Households to Catastrophic Expenditures of Oral and Dental Health Care in Ahvaz City - Ali feizi; Bahar Hafezi; Saeed Bagheri Faradonbeh; shahram Tofighi (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2023)
Background: The treatment of oral and dental diseases is expensive all over the world and these diseases are considered the fourth most expensive diseases. The aim of the present study is analysis of exposure of households to catastrophic expenditures of oral and dental health care in Ahvaz city. Methods: The present cross-sectional descriptive-analytical study was conducted on 715 households living in Ahvaz city in 2022using multistage sampling. Collecting the data was done through a questionnaire, and logistic model and Stata 17  software were used to analyze the data and estimate the elasticity of influencing factors. Results: According to the results of the study, the ratio of oral and dental health expenditures to household payment capacity was 59.03 %, and 52.16 % of households faced catastrophic expenditures. Also, supplementary insurances with Odd Ratio (OR) = 1.39, living in the southern region with OR = 1.08, and being in the 2nd income quintile with OR = 1.1 had a strengthening role in facing catastrophic expenditures. Conclusion: According to the results of this study, in order to reduce the negative effects of oral and dental health expenditures, it seems necessary to modify the financing policies of these services and move towards equity in financing through increasing insurance coverage.